Scientific Substantiation Of Nutritional Correction And Food Status Of School Age Children In Namangan Region - Tadjibaeva Gavharoy Ismailovna (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
In the article, it is learned to scientifically substantiate and implement organizational, hygienic and medical-preventive measures at the legislative and departmental levels aimed at reducing alimentary-dependent pathologies in schoolchildren of the Namangan region